Dengue Prevention and Control by Community Participation in Lamphun Province - เจาฑานนท์ บุษบง; หวังรุ่งทรัพย์ ปิยะพร; พูลถิน สุธีรา; เลิศวุฒิ กาญจนา; สิทธิโรจน์ เจริญ; ศิริวิบูรณ์ ไกรศิลป์; ลาวใส มนัส; กัณทะวารี สันติพงษ์; สายธรรม สุรินทร์ (Disease Control Journal, 2012)
This Participatory Action Research is aimed to develop a model of community participation for Dengue Prevention and Control through activities and participation by member of communities. The activities focused to build up the community ownership with health problem community assessment, community learning, training control measure and empowerment of community research teams. The results revealed that after implementation, the community set up a learning center. The community projects for reduction of larva breeding place and cleaning domestic waste products (home sweet home project) were carried out The outbreak investigation were done by the community members and the health networks were expanded from health volunteers to wife house groups and village leaders. This participatory action research was an important tool to facilitate and empower the community for developing the disease prevention and control. These results demonstrate the best practice of disease prevention and control model by community and should be modified to imply in the other communities.